Reformasi Tata Kelola Jaminan Produk Halal di Nusa Tenggara Barat: Strategi Memangkas Prosedur Berbelit dan Mengintegrasikan Lembaga - Samlan (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy article analyzes the challenges of implementing Halal Product Assurance (HPA) in West Nusa Tenggara (WNT), which is striving to position itself as a leading halal tourism destination. Despite a clear strategic vision and central government regulations, the halal certification process for Micro, Small, and Medium-sized Enterprises (MSMEs) still faces significant obstacles, particularly complex and time-consuming procedures. The main issues stem from the dual authority between the Halal Product Assurance Organizing Agency (BPJPH) and the Indonesian Ulema Council (MUI), a lack of integrated information systems among institutions, and inefficient audit procedures due to limited resources at the regional level. This situation not only burdens MSME actors and hinders the competitiveness of local products but also has the potential to damage the credibility of WNT's overall halal vision. Therefore, this article identifies the root causes of these problems and proposes strategic policy recommendations to reform HPA governance, streamline procedures, and integrate the roles of all stakeholders to create a more efficient, transparent, and competitive halal certification ecosystem.